Role of dental radiologists in diagnosis of patients with high risk of obstructive sleep apnea using lateral cephalogram: A case-control study - Syeda Arshiya Ara; Farahath Mujahid; Bhagyashree M Patil (Wolters Kluwer Medknow Publications, 2019)
Intoduction: OSA consists of repetitive short episodes of UA collapse with complete (apneas) or partial (hypopneas) obstruction of airway during sleep, associated with snoring and transient arousal, causing sleep fragmentation and insufficient and nonrestorative sleep. Aim: To recognize patients with high risk of obstructive sleep apnea using lateral cephalometric measurements in patients receiving routine dental treatment. Materials and Methods: The study was conducted on 120 patients, which were divided into two groups based on Berlin questionnaire which include 10 questions in 3 categories (snoring, day time drowsiness and hypertension/obesity) the study Group included 60 Patients and 60 normal patients. Digital Lateral Cephalometric analysis was done in all individuals to measure upper air way diameter (UAD), mandibular to hyoid distance (MHD) and to evaluate shape of soft palate (velar), by two observers at two different intervals. The data were statistically evaluated with student't' test and chi Square test using SPSS version 23.0.0. Results: The study comprised of 120 subjects who were divided into different age groups ranging from 18-65yrs. There were 61 males and 59 females when patients were divided according to gender and had no statistical significance. Based on Berlin questionnaire 51.7% were on high risk and 48.3% were on low risk. The UAD was reduced in study group than in control group and was statistically significant (P = 0.044). The MHD distance was increased in study group when compared with control group and was statistically highly significant (P < 0.001). No significant difference was found between groups when shape of soft palate was compared. Conclusion: Patients with lower UAD and higher MHD values are at high risk of developing OAS, dentist will play a vital role in diagnosis of these patients by thorough clinical examination & by cephalometric analysis.